Antioxidant Activity, Flavonoid and Phenolic Content of Mentha piperita Collected from Rupandehi, Nepal - Neupane, Umesh; Chidi, Gita; Pandey, Deepa; Bhandari, Manisha; Paudel, Keshav; Sharma, Krishna Prasad (Butwal Campus Journal, 2025)
Medicinal herbs from Himalaya’s country like Nepal are considered to have higher bioactive medicinal ingredients as compared to similar herbs from other regions. Preliminary phytochemical screening of Mentha piperita revealed the presence of alkaloids, terpenoids, flavonoids, phenols, tannins, saponins, glycosides, steroids, proteins, amino acids, and polyphenols, indicating rich bioactive composition. Quantitative analyses showed total phenolic content of 370.9 ± 6.45 mg GAE/ 100g dry weight and total flavonoid content of 345.0 ± 3.95 mg QE/ 100g dry weight, determined using Folin–Ciocalteu and aluminum chloride colorimetric assays, respectively. Antioxidant activity, assessed via the DPPH radical scavenging method, exhibited a concentration-dependent response, with % inhibition ranging from 22.40 ± 0.61% at 31.25 µg/mL to 84.89 ± 1.41% at 500 µg/mL. The IC₅₀ value was 156.06 ± 2.12 µg/mL with reference to standard ascorbic acid with an R² of 0.854, indicating a strong correlation between concentration and activity. These findings confirm Mentha piperita as a potent source of natural antioxidants, attributable to its high phenolic and flavonoid contents. The results support its traditional medicinal use and suggest potential applications in pharmaceutical, nutraceutical, and food preservation sectors.